2020
DOI: 10.1177/0885066620952763
|View full text |Cite
|
Sign up to set email alerts
|

Making Ventilator Associated Pneumonia Rate a Meaningful Quality Marker

Abstract: Introduction: Ventilator associated pneumonia (VAP) rate has been tracked as a comparable quality measure but there is significant variation between types of ICUs. We sought to understand variability and improve its utility as a marker of quality. Methods: The National Trauma Database was surveyed to identify risk factors for VAP. Logistic regression, χ2, Student’s T-test or Mann-Whitney U test were used. Results: Risk factors associated with developing VAP were: injury severity score (ISS) (OR 1.03, 95% CI 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…The relationship of AG with 30-day mortality was also observed in male, bacterial infection, and fungal infection subgroups. According to previous evidences, male gender and broad-spectrum antimicrobial therapy are acknowledged risk factors for the development of VAP ( 27 , 28 ). Different to our finding, López-de-Andrés et al ( 29 ) compared the incidence and in-hospital outcomes of VAP according to gender, and suggested that the in-hospital mortality rate for VAP was approximately 35% in patients of both genders.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship of AG with 30-day mortality was also observed in male, bacterial infection, and fungal infection subgroups. According to previous evidences, male gender and broad-spectrum antimicrobial therapy are acknowledged risk factors for the development of VAP ( 27 , 28 ). Different to our finding, López-de-Andrés et al ( 29 ) compared the incidence and in-hospital outcomes of VAP according to gender, and suggested that the in-hospital mortality rate for VAP was approximately 35% in patients of both genders.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing number of ventilator days was associated with increased odds of developing VAP which is consistent with previous studies 10 and expected as ventilation is a prerequisite for VAP. Multiple other studies have investigated risk factors for VAP in trauma patients finding increased risk for patients with chest trauma, [11][12][13][14] raised ISS, 11,14,15 head injury, 15,16 spinal cord injury, 13 low GCS, 17 delay in ICU admission 18 and pre-hospital intubation 17 or pre-hospital assisted ventilation. 14 A meta-analysis 19 of patients with traumatic brain injury found ISS, smoking, blood transfusion and barbiturate infusion to be associated with increased odds of VAP.…”
Section: Discussionmentioning
confidence: 99%